2009
DOI: 10.1089/jwh.2009.1488
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk in “Mostly Heterosexual” Young Women: Influence of Social Support and Caregiver Mental Health

Abstract: Background: Female youth who describe their sexual orientation as ''mostly heterosexual,'' rather than exclusively heterosexual, display greater sexual risk, yet reasons for this greater risk are not understood. Research is needed to identify factors responsible for health disparities in this population comprising the majority of youth who report a minority sexual orientation. Methods: We compared indicators of perceived social support, parental=caregiver mental health, and sexual risk (age at first sexual int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 25 publications
6
42
0
1
Order By: Relevance
“…78 Findings from previous studies have highlighted notable differences between "mostly heterosexuals" or "homosexually experienced heterosexuals" and other orientation groups. 57,58,79 Our findings suggest that unhealthy weight control behaviors may be particularly problematic among both male and female discordant heterosexuals. However, our analyses did not quantify the frequency of same-sex behavior, or the number of same-sex partners, and thus it is difficult to draw extensive conclusions on the basis of these findings.…”
Section: Discussionmentioning
confidence: 75%
“…78 Findings from previous studies have highlighted notable differences between "mostly heterosexuals" or "homosexually experienced heterosexuals" and other orientation groups. 57,58,79 Our findings suggest that unhealthy weight control behaviors may be particularly problematic among both male and female discordant heterosexuals. However, our analyses did not quantify the frequency of same-sex behavior, or the number of same-sex partners, and thus it is difficult to draw extensive conclusions on the basis of these findings.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, bisexual individuals engage in more self-injurious behaviors (Balsam et al, 2005) and suicidal ideation (Conron et al, 2010;Jorm et al, 2002) than gay, lesbian, and heterosexual people. Similarly, Corliss, Austin, Roberts, and Molnar (2009) found that young women who report some same-sex attraction but do not identify as lesbian or bisexual report higher levels of depression and problems with drug use than exclusively heterosexual individuals. These findings are in contrast to Zhao Montoro, Igartua, and Thombs' (2010) findings that adolescent youth who identify as heterosexual and have same-sex attraction or fantasy did not have increased suicidal ideation or attempts.…”
Section: Mental Health Of Sexual Minoritiesmentioning
confidence: 94%
“…Data have suggested that these women's reported rates of childhood abuse, risky sexual behavior, and substance abuse are similar to bisexual women's (Alvy et al, 2013;Austin et al, 2008;Corliss et al, 2009;Hughes et al, 2010b;Loosier and Dittus, 2010;McCabe et al, 2012). Although the reasons for these similarities are still unclear, mostly heterosexual and mostly lesbian women, as bisexual women, may experience marginalization and low levels of social support (Corliss et al, 2009;Hughes et al, 2010b).…”
Section: Introductionmentioning
confidence: 94%
“…First, studies have indicated non-monosexual women face mental health disparities compared to both heterosexual and lesbian women, and that mostly heterosexual and mostly lesbian women may be more similar to bisexual than to monosexual women (Alvy et al, 2013;Austin et al, 2008;Corliss et al, 2009;Hughes et al, 2010b;Loosier and Dittus, 2010;McCabe et al, 2012). Second, a meta-analysis found that bisexuality moderated the relationship between sexual orientation and childhood physical abuse; the differences between bisexual and heterosexual individuals were larger than those between gay/lesbian and heterosexual individuals (Friedman et al, 2011).…”
Section: Included Variablesmentioning
confidence: 99%